2016
DOI: 10.1007/s12928-016-0391-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous coronary artery dissection treated with biovascular scaffolds guided by intravascular ultrasounds imaging

Abstract: We reported a case of a fit and active 48 years' old woman presented with acute coronary syndrome due to a spontaneous coronary dissection (SCAD) treated with bioresorbable scaffolds (BVS) implantation guided by intravascular ultrasounds (IVUS) with immediate and long-term good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Ielasi et al of the RAI registry reported favorable procedural and clinical outcomes in 18 patients presenting with SCAD in ACS settings who were treated with Bioresorbable Vascular Scaffold (BVS, Absorb, Abbott Vascular, Santa Clara, CA). Similar results were achieved in single centre experiences at one‐year follow‐up . Nevertheless, the negative results of the ABSORB II and the ABSORB III trials at 3‐year and 2‐year follow‐up, respectively, raised important concerns about the increased risk of major adverse cardiovascular events with ABSORB scaffolds compared with XIENCE stents.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Ielasi et al of the RAI registry reported favorable procedural and clinical outcomes in 18 patients presenting with SCAD in ACS settings who were treated with Bioresorbable Vascular Scaffold (BVS, Absorb, Abbott Vascular, Santa Clara, CA). Similar results were achieved in single centre experiences at one‐year follow‐up . Nevertheless, the negative results of the ABSORB II and the ABSORB III trials at 3‐year and 2‐year follow‐up, respectively, raised important concerns about the increased risk of major adverse cardiovascular events with ABSORB scaffolds compared with XIENCE stents.…”
Section: Discussionsupporting
confidence: 62%
“…As a matter of fact, very extensive reconstructions are usually needed for SCAD, with the related concern for antiplatelet therapy optimal duration. For this reason, the use of bioresorbable scaffolds (BRS) is an attractive option and few cases of PCI with BRS in SCAD patients have been reported in the literature with good results. We reported a case of SCAD treated with a new magnesium‐made BRS.…”
Section: Introductionmentioning
confidence: 99%
“…The bioresorbable vascular scaffold (BVS) was approved by the Food and Drug Administration (FDA) 2010 and has been utilized in some case studies for SCAD [ 16 ] and has been considered for young patients with SCAD [ 15 , 17 19 ]. It is important to note that such use has not been validated and safety studies do demonstrate that BVS has a higher risk of thrombosis (3.5% versus 0.9%) in stent group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that such use has not been validated and safety studies do demonstrate that BVS has a higher risk of thrombosis (3.5% versus 0.9%) in stent group [ 16 ]. The theoretical advantage of BVS includes the restoration of the native vessel vasomotor and adaptive shear stress allowing for late luminal enlargement and late expansive remodeling once the scaffold degrades [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 53 Since then, some papers (mostly case reports and small series of patients) have described the usefulness of IVUS for: diagnostic confirmation of SCAD; as a guiding tool during PCI; and to confirm IMH has completely resolved on follow-up. [54][55][56][57][58][59] The experience OCT showed an intimo-medial dissection/fenestration in only 37% of the lesions. 52 During follow-up, OCT can be used to confirm vessel healing.…”
Section: Intravascular Ultrasoundmentioning
confidence: 98%